PENGARUH KUALITAS LAYANAN, ATMOSFIR TOKO TERHADAP PERILAKU PEMBELIAN ULANG MELALUI CITRA DAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pada Legend Coffee Yogyakarta) - Kurniawan, Handoko Bramantia; Bayu Dirgantara, I Made (Faculty of Economics and Business Diponegoro University, 2020)
In today's digital era, the phenomenon that occurs in millennials is that they often gather or carry out activities together with the closest people in a place such as in a cafÃ© or in places to eat. This is one of the lifestyle icons of the current millennial generation era, with the existence of a place to eat or cafÃ© can be used as a place to hang out or do activities with people nearby or even just to relieve fatigue from daily routine. This study aims to examine the effect of service quality, store atmosphere variables on repurchase behavior through image and customer satisfaction as an intervening variable. The study was conducted on Legend Coffe in the city of Yogyakarta.This study uses a purposive sampling technique with numbers a sample of 100 respondents. The method used in this study is the Structural Equation Model (SEM) using AMOS software 24.0.The results in this study indicate that service quality has a positive and significant effect on restaurant image variables, store atmosphere has a positive and significant effect on restaurant image variables, restaurant image variables have a positive and significant effect on customer satisfaction variables, customer satisfaction variables have a positive influence and significant to the variable intention to behave.